Towards QCD-assisted hydrodynamics for heavy-ion collision phenomenology - Dubla, Andrea; Masciocchi, Silvia; Pawlowski, Jan M.; Stachel, Johanna (Nuclear physics. A, Nuclear and hadronic physics, 2018)
Heavy-ion collisions are well described by a dynamical evolution with a long hydrodynamical phase. In this phase the properties of the strongly coupled quark-gluon plasma are reflected in the equation of state (EoS) and the transport coefficients, most prominently by the shear and bulk viscosity over entropy density ratios η/s(T) and ζ/s(T), respectively. While the EoS is by now known to a high accuracy, the transport coefficients and in particular their temperature and density dependence are not well known from first-principle computations yet, as well as the possible influence they can have once used in hydrodynamical simulations. In this work, the most recent QCD-based parameters are provided as input to the MUSIC framework. A ratio η/s(T) computed with a QCD based approach is used for the first time. The IP-Glasma model is used to describe the initial energy density distribution, and UrQMD for the dilute hadronic phase. Simulations are performed for Pb-Pb collisions at sNN=2.76 TeV, for different centrality intervals. The resulting kinematic distributions of the particles produced in the collisions are compared to data from the LHC, for several experimental observables. The high precision of the experimental results and the broad variety of observables considered allow to critically verify the quality of the description based on first-principle input to the hydrodynamic evolution.